Pengaruh Campuran Bioaditif Serai Wangi Pada Bensin RON 90 Terhadap Prestasi Mesin Dan Penghematan Bahan Bakar Sepeda Motor - Budi Utomo Wisesa; M. Yasep Setiawan; Ahmad Arif; Ari Aryadi; Ichsan Nasution (AEEJ : Journal of Automotive Engineering and Vocational Education, 2023)
Citronella is a variety of bioadditives that are easily soluble and evaporate into fuel. The use of Bioadditives in fuel aims to improve engine performance and fuel economy. The method used in this research is an experiment with RON 90 Gasoline samples, and a mixture of Citronella Bioadditives with a ratio of S1-1.5%, S2-2.0%, S3-2.5%, S4-3.0%, and S5-3.5%. Engine performance testing using Sportdevice Dyno and impacted engine performance increased by 3.11% on the S4-3.0% type, and maximum torque increase reached 2.03% on the S2-2.0% ratio. The fuel economy test based on the distance traveled with 1000 ml of fuel volume per sample at an average speed of 40-60 km/h was able to achieve a savings of 20.93% on the S5-3.5% sample with a distance of 69.9 Km/l. This is different from RON 90 gasoline without citronella mixture can only be traveled as far as 57.8 km / l. Serai Wangi merupakan ragam bioaditif yang bersifat mudah larut dan menguap ke dalam bahan bakar. Pemakaian Bioaditif dalam bahan bakar bertujuan untuk meningkatkan performa mesin dan penghematan bahan bakar. Metode yang dipakai dalam riset ini adalah eksperimen dengan sampel Bensin RON 90, dan campuran Bioaditif Serai Wangi dengan rasio S1-1,5%, S2-2,0%, S3-2,5%, S4-3,0%, dan S5-3,5%. Pengujian performa mesin mengunakan Sportdevice Dyno dan memberi dampak prestasi mesin meningkat sebesar 3,11 % pada jenis S4-3,0%, dan kenaikan torsi maksimum mencapai 2,03 % pada rasio S2-2,0%. Uji Penghematan bahan bakar berdasarkan jarak yang ditempuh dengan 1000 ml volume bahan bakar setiap sampel pada kecepatan rata-rata 40-60 km/jam mampu meraih penghematan sebesar 20,93% pada sampel S5-3.5% dengan jarak tempuh sejauh 69,9 Km/l. Hal ini berbeda dibandingkan dengan bensin RON 90 tanpa campuran serai wangi hanya mampu ditempuh sejauh 57,8 Km/l.